Livelihood strategies for widows and divorcees of coastal fishers in Indonesia - Subair, Nurlina; Pidani, Rita R.; Meiyani, Eliza; Haris, Risma; Irma, Irma (Department of Anthropology, Faculty of Social and Political Sciences, Hasanuddin University., 2023)
In Bugis-Makassar families with a patriarchal cultural system, men are the backbone of the family and women only work in the domestic realm. The main problem faced by widows and divorcees of coastal fishers is the dual role that requires them to take care of the household and children as well as earn a living for the needs of the family. This dual function requires a widow to have a strategy and carry out these two roles simultaneously. This study aims to find out how the strategies for making a living for widows of coastal fishers in improving the family economy. This study uses a qualitative approach with case study method. The data collection technique uses a purposive sampling for determining the informant and conducting in-depth interview technique with eight widows consisting of four widows and four divorcees. We also observed the daily activities of the informants. Meanwhile, the interview process was carried out using semi-structured interviews about how the strategy for earning a living was carried out so that it could support the family economy. The study found social capital-based livelihood strategies for poor fishers. They often interpret the strategy as a way or an alternative to a situation. In this case, the widow or divorcee of a coastal fisher is part of the community. Widows and divorcees who work in more than one type of work make their association with others as a form of social capital. Thus, they can provide support to each other as aform of social security and social capital to support the family.